2016
DOI: 10.1021/acs.jpcc.5b10215
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Optical Performance of BaMgAl10O17:Eu2+ Phosphor by a Novel Method of Carbon Coating

Abstract: Many strategies have been adopted to improve thermal degradation of phosphors. Because of the stability and high transmittance of graphene, here we report a novel method of carbon coating on BaMgAl 10 O 17 : Eu 2+ (BAM) phosphor particles through Chemical Vapor Deposition (CVD). The chemical composition, microstructure, and luminescence performance of carbon-coated BAM were characterized carefully. This coating can be controlled within 3-10 atomic layers, depending on the reaction time. Due to the decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…The internal quantum efficiency (IQE) and external quantum efficiency (EQE) of BAM is about 91% and 65%, respectively. To further improve the QE and thermal stability of BAM, carbon coating had been adopted by Yin et al via chemical vapor deposition (CVD) (Yin et al, 2016). The IQE and EQE were demonstrated to increase up to 95% and 76%, and the thermal degradation decreased from 20% to 4.6%.…”
Section: Introductionmentioning
confidence: 99%
“…The internal quantum efficiency (IQE) and external quantum efficiency (EQE) of BAM is about 91% and 65%, respectively. To further improve the QE and thermal stability of BAM, carbon coating had been adopted by Yin et al via chemical vapor deposition (CVD) (Yin et al, 2016). The IQE and EQE were demonstrated to increase up to 95% and 76%, and the thermal degradation decreased from 20% to 4.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the high pure blue phosphor is necessary for backlit display. However, the commercially available blue phosphor such as BaMgAl 10 O 17 :Eu 2+ (BAM:Eu 2+ ) could not completely meet the color purity requirement of backlit display due to the broad fwhm . Another reported blue emitting phosphors have either unsuitable excitation position or broad emission band, which are also not extensively applied in backlit display.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, it has been demonstrated that carbon coating deposited on the surface of BaMgAl 10 O 17 :Eu 2+ phosphors is an effective way to improve the intensity and thermal stability of oxide phosphors [22]. The carbon coated phosphors show a higher emission intensity and a better oxidation resistance at high temperature than uncoated phosphors.…”
Section: Introductionmentioning
confidence: 99%